Empowering citizens in digital health data governance: Insights from an overview of reviews - Cato van Schyndel; Charlotte De Clerck; Erik Laes; Karin Hannes; Nathalie Lambrechts (Big Data & Society, 2026)
As digital technologies in healthcare expand, critical discussions on protecting privacy, securing personal health data, and governing its use have gained prominence. Despite regulations such as the General Data Protection Regulation and the European Health Data Space, many citizens remain unaware of their data rights or how their data are used. This highlights the need to understand how citizens wish to participate and what meaningful participation entails. This overview of reviews synthesizes insights from 35 systematic reviews (2011–2023) on citizen participation in health data governance, including reviews in which citizens’ broader views on health data use, which influence willingness and ability to participate, are discussed. Findings are interpreted through the lens of feasibility, appropriateness, meaningfulness, and effectiveness. Findings highlight the complexity of fostering citizen participation in health data governance. While citizens often express favorable attitudes, the way they are currently involved remains largely tokenistic, limited to informing, consultation, or placation. Strengthening participation requires attention to feasibility, appropriateness, and meaningfulness of citizen-driven data governance. Findings suggest that building trust and accountability, ensuring digital and health literacy, involving trusted intermediaries, and recognizing the sensitivity of data are beneficial. Participation is most meaningful when it delivers both personal benefits (e.g. improved care) and public benefits (e.g. advancing research). Effectiveness arises when these conditions work together, enabling participation to move beyond tokenism and deliver tangible improvements for citizens and society.